2020
DOI: 10.3389/fmicb.2020.548607
|View full text |Cite
|
Sign up to set email alerts
|

Total Arsenic, pH, and Sulfate Are the Main Environmental Factors Affecting the Microbial Ecology of the Water and Sediments in Hulun Lake, China

Abstract: Bacteria have the metabolic potential to produce a diverse array of secondary metabolites, which have important roles in biogeochemical cycling processes. However, for Hulun Lake and the rivers that enter into it, the bacterial community structures and their effects have not previously been widely studied, limiting our ecological understanding of this habitat. To address this, we have analyzed the bacterial communities in the water ecosystem of the Hulun Lake Basin. 16S rRNA highthroughput sequencing identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 65 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…For bacteria and archaea, we found that variations in total LCBD and LCBD Repl were greatly contributed by the water factors such as NO 3 − -N or NO 2 − -N ( Figure 4A ), which may be related to eutrophication and the local climates. Hulun Lake, as a large hypereutrophic steppe lake, has clearly shown that microbial taxa such as bacteria and archaea frequently participate in the cycling of carbon, nitrogen and phosphorus in aquatic ecosystem ( Shang et al, 2020 ). Over the past few years, however, the warming and drying climate has gradually accelerated the shrinking of water area and the decrease of water level in Hulun Lake ( Cai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For bacteria and archaea, we found that variations in total LCBD and LCBD Repl were greatly contributed by the water factors such as NO 3 − -N or NO 2 − -N ( Figure 4A ), which may be related to eutrophication and the local climates. Hulun Lake, as a large hypereutrophic steppe lake, has clearly shown that microbial taxa such as bacteria and archaea frequently participate in the cycling of carbon, nitrogen and phosphorus in aquatic ecosystem ( Shang et al, 2020 ). Over the past few years, however, the warming and drying climate has gradually accelerated the shrinking of water area and the decrease of water level in Hulun Lake ( Cai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results were accurate to the last two decimal places. The contents of total nitrogen and total organic carbon were determined by using multi N/C 3100 analyzer with reference to Kirschler sodium benzoate method, combustion oxidation method and non-dispersive infrared method (Wang et al 2020 ; Sui et al 2021 ; Shang et al 2020 ; Chen et al, 2023 ). All the experimental processes were completed in the Experimental Center of the College of Life Science, Qufu Normal University.…”
Section: Methodsmentioning
confidence: 99%
“…When the microbial population in the lake water decreases, the nutrient cycles shift, and a cyclic process is produced. The structure of microphytic communities is in uenced by a variety of environmental factors (Shang et al 2020). Several different indexes are used in ecological investigations.…”
Section: α-Diversity and Rarefaction Curvesmentioning
confidence: 99%